2021
DOI: 10.1186/s40795-021-00479-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition literacy is associated with income and place of residence but not with diet behavior and food security in the Palestinian society

Abstract: Introduction Palestinian society is going through health transition that is associated with increase in chronic diseases due to poor dietary habits so adequate integration of nutrition information is important. Aims The aim of this study is to find the association between nutrition literacy and diet behavior among a group of Palestinian participants. Methods A sample of 101 Palestinian participants wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 32 publications
(30 reference statements)
3
27
2
Order By: Relevance
“…Our previous studies found that BMI is a determinant of NL among middle school students in Chongqing, China ( 24 ). Using multinomial logistic regression model and subgroup analyses, our findings suggested inverse relationships between NL, FNL, and overweight/obesity, different from some previous studies ( 11 , 18 ). Several explanations were considered for these findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our previous studies found that BMI is a determinant of NL among middle school students in Chongqing, China ( 24 ). Using multinomial logistic regression model and subgroup analyses, our findings suggested inverse relationships between NL, FNL, and overweight/obesity, different from some previous studies ( 11 , 18 ). Several explanations were considered for these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Existing studies on the association between NL and overweight/obesity were primarily conducted in adults ( 17 ). One study has revealed no association between NL with BMI ( 18 ). However, another research has shown that lower NL is more problematic for weight loss ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, income is one of the crucial indicators that could show the impact of socio-economic status on nutrition literacy ( 28 ). Corroborating the finding of other previous studies ( 32 , 43 , 57 ), the present findings show that respondents with a family income above 40,000 BDT/month reported higher nutrition literacy scores.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study among adults in Sivas province of Turkey reported a correlation between the mean nutrition literacy scores and variables such as gender, education and profession ( 27 ). A recent study among Palestinian adults demonstrated that nutrition literacy is associated with income and place of residence ( 28 ). The nutrition status of individuals living in South Asia has been well documented ( 29 , 30 ), yet, the knowledge on risk factors associated with adults’ nutrition literacy is minimal, specifically in Bangladesh a country with a significant level of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation